2016
DOI: 10.1111/vco.12264
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation ofCOX‐2 expression, histological and clinical factors as prognostic indicators in dogs with renal cell carcinomas undergoing nephrectomy

Abstract: Limited veterinary literature is available regarding prognostic markers for canine renal cell carcinoma (CRCC). We retrospectively evaluated COX-2 expression, histological and clinical features associated with prognosis of CRCC. Sixty-four cases post-nephrectomy were included, 54 had histopathological assessment and 30 had COX-2 immunostaining performed. Eight dogs (13%) had metastatic disease at initial diagnosis. Twenty-seven dogs (42%) received adjuvant therapy after nephrectomy. On univariate analysis, COX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 44 publications
(65 reference statements)
1
34
0
Order By: Relevance
“…Interestingly, our study shows that ePSCCs overexpress COX-2 in a high proportion of cases as occurs in invasive hPSCC but also esophageal SCC [30,31]. The use of COX-2 inhibitors alone or as part of a multimodal therapy to aid in the treatment of the disease is a field of current research in human and veterinary medicine [10,11,32]. To illustrate this, in veterinary medicine…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, our study shows that ePSCCs overexpress COX-2 in a high proportion of cases as occurs in invasive hPSCC but also esophageal SCC [30,31]. The use of COX-2 inhibitors alone or as part of a multimodal therapy to aid in the treatment of the disease is a field of current research in human and veterinary medicine [10,11,32]. To illustrate this, in veterinary medicine…”
Section: Discussionmentioning
confidence: 92%
“…Mohammed et al [9] reported a reduction in tumor volume in 12 of 18 dogs due to induction of apoptosis caused by piroxicam. COX enzymes catalyze the rate-limiting step of prostaglandin biosynthesis and are involved in inhibiting apoptosis, promoting cell proliferation, stimulating angiogenesis, and decreasing immunity [10]. In general, COX-1 is present in several normal tissues, and COX-2 is expressed in multiple neoplasms and inflammatory cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…Their ultrasonographic and radiological appearance was suggestive of RCC and pulmonary metastasis. Most metastasis in a study of canine RCC was pulmonary 22 . Interestingly, 85% of dogs with metastasis at time of diagnosis had evidence of vascular invasion on histopathological examination 22 .…”
Section: Discussionmentioning
confidence: 99%